2001
DOI: 10.1128/jb.183.3.854-864.2001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Symbiotic Performance by Rhizobium tropici Glycogen Synthase Mutants

Abstract: We isolated a Tn5-induced Rhizobium tropici mutant that has enhanced capacity to oxidize N,N-dimethylp-phenylendiamine (DMPD) and therefore has enhanced respiration via cytochrome oxidase. The mutant had increased levels of the cytochromes c 1 and CycM and a small increase in the amount of cytochrome aa 3 . In plant tests, the mutant increased the dry weight of Phaseolus vulgaris plants by 20 to 38% compared with the control strain, thus showing significantly enhanced symbiotic performance. The predicted produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 55 publications
4
27
0
4
Order By: Relevance
“…A possible physiological explanation for the increase in nitrogen fixation rate could be that the increase of reductive power (lower NAD/NADH ratio) can be channeled to nitrogen fixation [22]. A similar effect on symbiotic nitrogen fixation is predicted for the glycogen synthase deletion, which also agrees with the observed physiological response reported for Rhizobium tropici [36]. FBA suggests that the same effect would occur for R. etli.…”
Section: Gene Deletion Analysissupporting
confidence: 80%
“…A possible physiological explanation for the increase in nitrogen fixation rate could be that the increase of reductive power (lower NAD/NADH ratio) can be channeled to nitrogen fixation [22]. A similar effect on symbiotic nitrogen fixation is predicted for the glycogen synthase deletion, which also agrees with the observed physiological response reported for Rhizobium tropici [36]. FBA suggests that the same effect would occur for R. etli.…”
Section: Gene Deletion Analysissupporting
confidence: 80%
“…The concentration of PHB was determined from cells grown in YMB medium, using a spectrophotometric technique (17) as modified by Peoples and Sinskey (23). The exopolysaccharide (EPS) content was determined as previously described (20), using cultures grown in YMB for 4 days at 30°C. Glycogen was extracted from cells and determined by anthrone assay according to the procedure of Chun and Yin (6).…”
Section: Methodsmentioning
confidence: 99%
“…The roles of PHB and glycogen in rhizobia-legume symbiosis are not fully understood (Lodwig & Poole, 2003;Mandon et al, 1998;Marroqui et al, 2001;Trainer & Charles, 2006). For instance, bacteroids of determinate nodules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A common genetic organization of the glycogen metabolism genes is found in the closely related Agrobacterium tumefaciens, Rhizobium tropici, Rhizobium leguminosarum and Mesorhizobium loti, within the glgPBCApgm operon (Lepek et al, 2002). Through analysis of a glgA mutant of R. tropici, it has been shown that there may be a link between glycogen synthase deficiency, decreased EPS, and increased symbiotic performance during symbiosis with Phaseolus vulgaris (Marroqui et al, 2001). However, the reason for the increased symbiotic efficiency of the glgA mutant is uncertain (Lodwig & Poole, 2003).…”
Section: Introductionmentioning
confidence: 99%